Effect of an Online Mindfulness Course for Hospital Doctors During COVID-19 Pandemic on Resilience and Coping - Petra Hanson; Manuel Villarreal; Majid Khan; Jeremy Dale; Sailesh Sankar (SAGE Publishing, 2022)
Introduction: Physicians' wellbeing is a priority to prevent increasing rates of poor mental health and burnout, exacerbated by caregiving during the COVID-19 pandemic. Structured mindfulness courses have been shown to be beneficial, but face-to-face delivery is not always feasible in the context of busy health services. Remotely delivered structured mindfulness courses could enable wider participation, particularly at time when social distancing to prevent infection transmission is necessary. Our objective was to test the feasibility of a remotely delivered structured mindfulness course for hospital doctors during the COVID-19 pandemic. Methods: This was a feasibility study run at one English hospital between January and March 2021, when COVID-19 admissions were at a high. Interested doctors participated in a 6-session remotely delivered mindfulness course. Sessions lasted 90 min and could be attended on-line or the recording watched at later time. Main outcome measures were data on interest, course attendance and engagement, together with validated psychological outcome measures at baseline and follow-up after course completion. Results: 20 doctors expressed interest to participate and 16 started the course. Of these, 12 completed at least 3 sessions (median = 4); difficulty attending resulted from conflicting clinical commitments and rosters. Twelve participants completed the follow-up survey. They rated the course highly and all perceived it to have been useful, with statistically significant ( P  < .01) improvements in wellbeing and mindfulness scores. They all stated that they would recommend this course to their colleagues and most (10/12) were interested in follow-up mindfulness sessions. Conclusion: Remotely delivered structured mindfulness training for hospital doctors was feasible, but there is a need to address the difficulties that affected attendance in order to optimize accessibility and completion of such programs.